IMPLEMENTASI KEBIJAKAN KARTU IDENTITAS ANAK (KIA) DI DINAS KEPENDUDUKAN DAN CATATAN SIPIL KOTA TASIKMALAYA - Nidia Rismania Dewi (JURNAL ILMIAH ILMU ADMINISTRASI, 2020)
This research is entitled "Implementation of the Child Identity Card (KIA) Policy in the Population and Civil Registry Office of Tasikmalaya City"."The research method used is the qualitative research method. According to Bogdan in Moleong (2007: 4) explains that "Qualitative Method is a research procedure that produces descriptive data in the form of written or oral words from people and observable behavior". To get an intensive, in-depth, detailed and complete qualitative analysis, the data collection in this study will use data sources namely Observation, Interviews and Use of Documents. Every Child is required to have this Child Identity Card (MCH) listed in Permendagri No. 2 of 2016. KIA at the Tasikmalaya City Population Service is still aimed at improving Data Collection, Protection, and Fulfillment of Children's Rights. Data collection techniques in this study using observation, interviews, and documentation. Research Methods using descriptive research methods with a quantitative approach. Research Results Also The discussion in this MCH policy research was felt to be still lacking because a lot of Tasikmalaya residents especially the city of Tasikmalaya did not know much about what is a Child Identity Card (MCH) and the benefits of the MCH itself.Keywords: Police implementation, Child Identity Card,